DAMPAK EKONOMI EKSPOR PERDAGANGAN BATIK INDONESIA KE AMERIKA SERIKAT TAHUN 2010-2014 - Dyana Novita Ningsih; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This Research describes that the economic impact of Indonesian batik trade exports to the United States in 2010-2014. This study will look at how far the export activities can affect economic relations for Indonesia and the United States. This study also tried to analyze the impact of the export trade of batik Indonesia in terms of the economic aspects. Researher are keen to discuss the economic impact of Indonesian batik trade export to the United States in 2010-2014 to see how far the export activities can affect economic relations for Indonesia and the United States.This research uses qualitative-analysis method. The datas were obtained from internet, journals, and books. Then, they were collected, summarized and analyzed based on the social research method. This research uses export theory and international cooperation theory. In this research, writers uses theories that support this research appropriate with economic-politic studies.This research explores the issue of economic impacts of Indonesian batik trade exports to the United States in 2010-2014, is to see how far the Indonesian batik exports to the United States is able to influence the foreign exchange Indonesia. Economic impact of Indonesian batik exports to the United States is increase foreign exchange for Indonesia.Key Words: Export, Trade, Indonesian Batik, United States, Economic Aspects.